Neuromorpha vorax: a previously unculturable cosmopolitan protist with an unexpectedly complex life cycle belonging to Glissomonadida Clade-U/Group-TE - Gabrielle Corso; Lindsay R. Triplett; Daniel J. Gage (mBio)
ABSTRACT Soil protists are increasingly recognized as common members of complex communities that associate with plant root systems, though their contributions to these communities and to the plant host remain obscure. Members of Clade-U/Group-TE are cosmopolitan soil protists and often among the most abundant protists associated with plant roots. Here, we describe the isolation, culturing, and characterization of Neuromorpha vorax, a member of the previously uncultured Clade-U/Group-TE branch of the order Glissomonadida. N. vorax grew readily when provided bacteriophage lysate as a food source. This allowed us to grow large numbers of the organisms from single-cell isolates and provided ideal conditions for following transitions from one morphology to another. N. vorax, like most glissomonads, has a small, flagellated gliding form, but it also displays a wide range of other morphologies, including a crawling form, small and large trophozoites with multiple long filopodia, small and large resting cysts, and clusters of large dividing cells, and cannibalistic feeding behaviors. Given the small size of most glissomonads, it may be that other members of this important group, known from environmental surveys but currently uncultured, might also be readily grown on bacteriophage lysates. In addition, given an abundant food source and clear viewing by microscopy, glissomonads and other small protists may be found to have life cycles and behaviors that are more complex than is currently appreciated.IMPORTANCEProtists from the Clade-U/Group-TE cluster of glissomonads are widespread and abundant colonizers of plant roots. Despite being known for over 30 years, they have remained uncultured. We show that these protists can be easily cultured using an unusual food source, viral lysates of bacteria. This culturing method allows growth of high numbers of these organisms and reveals that they have an unexpectedly complex lifecycle that includes community feeding and cannibalism. Some other currently unculturable protists can perhaps be grown with these methods, and many of these may also show unexpectedly complex lifecycles. The growth of eukaryotes on virus lysates raises the possibility that viruses in soil may directly contribute to the growth (and not just death) of eukaryotes in soil and root-associated communities.